Digital Tools in Cross-Cultural Analysis of Sme Financial State Support in the Conditions of Pandemic Crisis - Alla Ivashchenko; Yuliia Kovalenko; Oleh Hubanov; Tamara Hubanova; Iryna Lutsenko; Anastasiia Fialkovska (Journal of Information Technology Management)
The main goal of the given research is to conduct cross-cultural analysis of financial support mechanisms in Europe in order to develop practical recommendations, focused on SME recovery, for emerging markets, in particular Ukraine. The article examines the main effects of pandemic on economy, focusing on business disruption, in particular SME. The financial flows as a response on anti-pandemic prevention measures were analyzed all over the world through digital tools, namely BI, as well as differentiation of support measures. The general fall in the main macroeconomic indicators was indicated for European countries and the deep analysis of financial support mechanisms provided by states was conducted. Taking into account research results, it was revealed that complex policy mechanisms were developed mainly by advanced economies while emerging markets, in particular Ukraine, do not have the effective mechanisms aimed at eliminating negative effects of pandemic. So, on the basis of conducted analysis the practical recommendations for emerging markets, in particular Ukraine, were developed using relevant European experience